2006
DOI: 10.1002/cbdv.200690120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Permeation through Phosphatidylcholine Bilayers ofN-Dipicolinyl-α- and -β-Oligopeptides

Abstract: Cell-membrane permeation of small therapeutic peptides and peptidomimetics is a fundamental issue in pharmaceutical research. Using a Tb(3+)-based permeation assay, we have examined the ability of alpha- and beta-peptides, bearing proteinogenic side chains and an N-terminal dipicolinic acid (DPA) monoamide group, to enter liposomes composed of egg phosphatidylcholine bilayers. A series of 12 DPA-peptides of increasing chain length was prepared and characterized by CD and NMR analysis. An interesting destabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The CD spectral evidence for AcSC 15 B 6 Fc in TFE indicates this peptide adopts a 10/12-helix, which is typically not favored by these peptides and considered unlikely (however, CD studies are not always accurate, and structural determinations based solely on CD are unwise). 24,25 Finally, ellipsometry on the SAM Fc used in this study gave an average film thickness = 4.3 ((0.3) nm, which compares with 0.8 nm for lipoic acidÀ (β 3 Val-β 3 Ala-β 3 Leu) 2 ÀFc. 10 Long-chain alkyl thiolates are exceptionally good at forming compact and well-ordered SAMs, 26À28 but this ability is offset by any bulkiness in terminal moieties that can reduce the film compactness.…”
Section: ' Results and Discussionmentioning
confidence: 65%
“…The CD spectral evidence for AcSC 15 B 6 Fc in TFE indicates this peptide adopts a 10/12-helix, which is typically not favored by these peptides and considered unlikely (however, CD studies are not always accurate, and structural determinations based solely on CD are unwise). 24,25 Finally, ellipsometry on the SAM Fc used in this study gave an average film thickness = 4.3 ((0.3) nm, which compares with 0.8 nm for lipoic acidÀ (β 3 Val-β 3 Ala-β 3 Leu) 2 ÀFc. 10 Long-chain alkyl thiolates are exceptionally good at forming compact and well-ordered SAMs, 26À28 but this ability is offset by any bulkiness in terminal moieties that can reduce the film compactness.…”
Section: ' Results and Discussionmentioning
confidence: 65%
“…Fluorescence spectroscopy has been used to quantify the kinetics of drug permeation through model membranes similar to those studied computationally, i.e., lipid bilayers composed of either a single type of lipid (e.g., phospholipid) or a mixture of two lipids (e.g., phospholipid and cholesterol). These approaches, however, require that the permeant itself is fluorescent or exhibits self-quenching fluorescence. An alternative approach utilizing the photoluminescence of lanthanides has also been developed. However, in this case, the permeant is required to both absorb in a convenient wavelength window and chelate the lanthanide ion . Furthermore, there is evidence that some of these latter studies are prone to experimental artifact …”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, it is often assumed that the lipid-bilayer permeation of the ionized species of a weak acid or a base is negligible at physiological pH. We found that the anions of several aromatic carboxylic acids controlled permeation across egg phosphatidylcholine bilayers at pH 7 [3] [4] [41]. This was concluded from the fact that the pH -permeation profiles, which perfectly fitted Hendersson -Hasselbalch functions with inflection points at pH ¼ pK a , reached the plateau of ion permeation at pH values < 7.…”
Section: What If Not the Same Process Is Rate-limiting At Low And Higmentioning
confidence: 99%